Spontaneous Coronary Artery Dissection of LM and LM- LAD artery in Peripartum or Postpartum Women with Acute Myocardial Infarction (Cardiovascular Journal, 2015)
Spontaneous coronary artery dissection (SCAD) is a very rare condition which may result in sudden coronary occlusion, acute myocardial infarction and sudden cardiac death. It usually occurs in young women during pregnancy or postpartum period and in most cases it involves a single coronary artery. The exact etiology is unknown. The prognosis of SCAD is uncertain and optimal treatment is unknown. Early diagnosis and treatment are key for survival, and when identified early, mortality rate is reduced. DOI: http://dx.doi.org/10.3329/cardio.v7i2.22265 Cardiovasc. j. 2015; 7(2): 153-158